PENGARUH KOMPLEKSITAS PERUSAHAAN DAN RISIKO PERUSAHAAN TERHADAP BIAYA AUDIT (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2018-2021) - Tiara Poetri Ajeng Ariyanto; Wiwi Idawati (Ibs Press, 2023)
This study aims to determine and examine the effect of company complexity and company risk on audit fees. The sample of this research is manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2021. Sampling is carried out using the purposive sampling method with the number of companies that meet the criteria as many as 64 companies. The type of data used in this research is quantitative data. The source of data in this study is secondary data. The data analysis technique of this research uses multiple linear regression analysis using EViews 10. The dependent variable used is audit fees. The independent variables used are company complexity and company risk. The results show that the complexity of the company has a positive effect on audit fees. In addition, this study shows that the results of the company's risk as measured by the leverage ratio have no effect on audit fees.